Penggaruh Blended Learning Tipe Flipped Classroom Dengan Media Kahoot Terhadap Hasil Belajar Peserta Didik Kelas XI SAMA Negeri 1 Sukoharjo - Tantri Murti Sari; Kristiani Kristiani; Leny Noviani (Departement of Mathematics Education, 2023)
This study aims to determine the effect of using the flipped classroom-type blended learning model with Kahoot media on the learning outcomes of class XI students at SMA Negeri 1 Sukoharjo. The research method used is a quasi-experimental quantitative design. Data collection techniques to measure learning outcomes are taken using a pre-test and post-test. Data analysis techniques used the normality test, homogeneity test, and hypothesis testing using the t-test data analysis technique. The results of this study showed an increase in the average learning outcomes of the experimental class by 18.33% with the class completeness criteria increasing by 51.5% after receiving learning using the blended learning flipped classroom model with Kahoot media. The results of the independent sample t-test yielded 2.976 > 1.995 with a probability value of 0.004 <0.05 so the research hypothesis was accepted. It is known that there is a positive influence of the blended learning flipped classroom learning model using Kahoot media on learning outcomes in the economics subject